SARS-CoV-2 and the implications of high intensity training - Boukelia, B.; Fogarty, M.; Sabba, A. (International Journal of Sport, Exercise and Health Research, 2020)
The rapid spread of the virus that causes COVID-19 (SARS-CoV-2) has sparked alarm worldwide. The way the virus spreads is still unclear; however, it`s known that similar viruses are spread in cough & sneeze droplets. At the time of writing this editorial over 300,000 people worldwide have been infected with over 13,000 deaths (WHO, 2020). The principle measure introduced to stop the spread of infection among the general population is by encouraging the public to undertake specific behaviours related to hygiene, that is useful in stopping the spread amongst family members or close associates for previous outbreaks of virus from the same family. A second measure used widely across the worldis social distancing for non-infected members of the public or social isolation for infected families or high-risk individuals. Many sporting events and athletic games have been postponed causing large scale disruption to the global sport industry with millions of dollars lost. Most teams and induvial athletes will continue to train to maintain fitness and be ready for the return to active competition when the pandemic is under control.